Prognostic factors for survival in patients with metastatic malign melanoma treated with ipilimumab: Turkish Oncology Group study. (October 2019) - Urun, Yuksel; Yasar, H Arzu; Turna, Hande; Esin, Ece; Sedef, A Murat; Alkan, Ali; Oksuzoglu, Berna; Ozdemir, Nuriye; Sendur, MA Nahit; Sezer, Ahmet; Kılıckap, Saadettin; Utkan, Gungor; et al.
Purpose: Studies in the last decade show survival improvement with checkpoint blocker therapy in patients with metastatic malign melanoma. Our purpose was to define the efficacy of ipilimumab according to the patient's baseline characteristics including absolute lymphocytes count. Methods: We collected the data of 97 patients with advanced malign melanoma treated with ipilimumab (3 mg/kg, q3w) retrospectively. Log-rank test was used to analyze the univariate effects of patient's characteristics (age, gender, metastatic sites, ECOG PS, type of melanoma, lactic dehydrogenase levels, anemia, lymphocytes (L), neutrophils (N), N/L ratio), c-kit and BRAF status. Survival analyses were estimated with Kaplan–Meier method. Cox regression analysis was used to assess the possible factors identified with log-rank test. Results: The median age was 58, and 58% were male and 90% of patients had at least one prior systemic therapy. The median survival was 9.7 months for all patients; and the 12- and 24-month survival rates were 43% and 19%, respectively. Absolute lymphocytes count, lactic dehydrogenase level, bone metastasis, the number of metastatic sites, and RECIST response were significantly related to survival. After Cox regression analysis, RECIST response (complete or partial response), absolute lymphocytes count (more than 1500/mm 3 ) and the number of metastatic sites (less than three sites) remained as significant independent prognostic factors for longer survival. Conclusion: Ipilimumab improved survival of patients with metastatic malign melanoma. However, patients with fewer metastatic sites and higher absolute lymphocytes count have a significantly better benefit. To determine if these markers could be used to direct patient therapy, further validation analysis is needed.